Small vessel disease is associated with an unfavourable outcome in stroke patients on oral anticoagulation. (March 2020) - Hert, Lisa; Polymeris, Alexandros A.; Schaedelin, Sabine; Lieb, Johanna; Seiffge, David J.; Traenka, Christopher; Fladt, Joachim; Thilemann, Sebastian; Gensicke, Henrik; De Marchis, Gian Marco; Bonati, Leo; Lyrer, Philippe; et al.
Introduction: Cerebral small vessel disease is an important cause for both ischaemic stroke and intracranial haemorrhage. To date, knowledge on the impact of small vessel disease on the clinical course in stroke patients treated with oral anticoagulation for atrial fibrillation is limited. Patients and Methods: Registry-based prospective observational study of 320 patients (aged 78.2 ± 9.2 years) treated with anticoagulation following atrial fibrillation stroke. Patients underwent standardised magnetic-resonance-imaging assessing measures of small vessel disease, including cerebral microbleeds and white matter hyperintensities. Median follow-up was 754 (interquartile range = [708–828]) days. Using adjusted logistic and Cox regression, we assessed the association of imaging measures with clinical outcome including recurrent ischaemic stroke, intracranial haemorrhage and death and assessed disability (modified Rankin Scale). Results: Overall, recurrent ischaemic stroke was more common than intracranial haemorrhage (22 versus 8, respectively). Cerebral microbleeds were related to an increased risk of the composite endpoint (ischaemic stroke, intracranial haemorrhage, death: odds ratio (OR) 2.05, 95% confidence interval (CI) 1.27–3.31; P  = 0.003), as were white matter hyperintensities (OR 2.00, 95%CI 1.23–3.27, P  = 0.005). This was also true in time-to-event analysis (cerebral microbleeds: HR 2.31, 95%CI 1.39–3.52; P  < 0.001; white matter hyperintensities: HR 1.99, 95%CI 1.20–3.17; P  = 0.007). Both measures were associated with an increased risk for recurrent ischaemic stroke (cerebral microbleeds: HR 4.42, 95%CI 1.07–18.20; P  = 0.04; white matter hyperintensities: HR 5.27, 95%CI 1.08–25.79, P  = 0.04) and intracranial haemorrhage (cerebral microbleeds: HR 2.43, 95%CI 1.04–5.69; P  = 0.04; white matter hyperintensities: HR 2.57, 95%CI 1.11–5.98, P  = 0.03). Furthermore, confluent white matter hyperintensities were associated with increased disability (OR 4.03; 95%CI 2.16–7.52; P  < 0.001) and mortality (HR 1.81, 95%CI 1.04–3.14, P  = 0.04). Discussion and conclusion: In atrial fibrillation stroke patients treated with oral anticoagulation, small vessel disease is associated with an unfavourable outcome. The presence of microbleeds indicated a risk higher for recurrent ischaemic stroke than for intracranial haemorrhage.